Dental pulp tissue engineering - Demarco,Flávio Fernando (2011)
Dental pulp is a highly specialized mesenchymal tissue that has a limited regeneration capacity due to anatomical arrangement and post-mitotic nature of odontoblastic cells. Entire pulp amputation followed by pulp space disinfection and filling with an artificial material cause loss of a significant amount of dentin leaving as life-lasting sequelae a non-vital and weakened tooth. However, regenerative endodontics is an emerging field of modern tissue engineering that has demonstrated promising results using stem cells associated with scaffolds and responsive molecules. Thereby, this article reviews the most recent endeavors to regenerate pulp tissue based on tissue engineering principles and provides insightful information to readers about the different aspects involved in tissue engineering. Here, we speculate that the search for the ideal combination of cells, scaffolds, and morphogenic factors for dental pulp tissue engineering may be extended over future years and result in significant advances in other areas of dental and craniofacial research. The findings collected in this literature review show that we are now at a stage in which engineering a complex tissue, such as the dental pulp, is no longer an unachievable goal and the next decade will certainly be an exciting time for dental and craniofacial research.